2005
DOI: 10.1160/th04-12-0834
|View full text |Cite
|
Sign up to set email alerts
|

Domain 5 of cleaved high molecular weight kininogen inhibits endothelial cell migration through Akt

Abstract: Domain 5 (D5) of cleaved high molecular weight kininogen (HKa) inhibits angiogenesis in vivo and endothelial cell migration in vitro, but the cell signaling pathways involved in HKa and D5 inhibition of endothelial cell migration are incompletely delineated. This study examines the mechanism of HKa and D5 inhibition of two potent stimulators of endothelial cell migration, sphingosine 1-phosphate (S1P) and vascular endothelial growth factor (VEGF), that act through the P13-kinase-Akt signaling pathway. HKa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The concentration (600 nmol/L) used is lower than the dose necessary for the inhibition of EC migration. 17 As indicated in Figure 3D, ␣v␤3 integrin formed a complex with uPAR and caveolin-1 only in the membrane rafts, but not in the nonraft fractions. D5 dissociated uPAR and caveolin-1 from ␣v␤3 integrin in the membrane rafts ( Figure 3D), suggesting D5 disrupts this complex formation via binding to membrane rafts.…”
Section: D5 Dissociates Upar-␣v␤3 Integrin Complex In the Membrane Ramentioning
confidence: 75%
See 1 more Smart Citation
“…The concentration (600 nmol/L) used is lower than the dose necessary for the inhibition of EC migration. 17 As indicated in Figure 3D, ␣v␤3 integrin formed a complex with uPAR and caveolin-1 only in the membrane rafts, but not in the nonraft fractions. D5 dissociated uPAR and caveolin-1 from ␣v␤3 integrin in the membrane rafts ( Figure 3D), suggesting D5 disrupts this complex formation via binding to membrane rafts.…”
Section: D5 Dissociates Upar-␣v␤3 Integrin Complex In the Membrane Ramentioning
confidence: 75%
“…Because the association of uPAR with ␣v␤3 integrin is resistant to removal of cholesterol, the interaction between uPAR and ␣v␤3 integrin seems direct, in agreement with the finding of Degryse et al that direct binding of uPAR to ␣v␤3 integrin occurs a region of uPAR domain 2. 29 Because D5 binds to the D2 domain of uPAR, and an antibody against uPAR restores HKa inhibition of EC migration on Vn, 17 uPAR is a primary binding site for HKa inhibition of ␣v␤3 integrin function. D5 occupancy of uPAR may not only block internalization of both receptors and the turnover of focal adhesion plaques during EC migration, but also prevent the assembly of reexpressed uPAR and integrin on the membrane surface during receptor cycling.…”
Section: Discussionmentioning
confidence: 99%
“…21,39 However, PI3K and p44/42 MAPK signaling pathway are less important to S1P-induced vascular endothelial cell migration. 21,28,[40][41][42] Furthermore, whether the involvement of the p38 MAPK pathway is important to S1P-induced vascular endothelial cell migration remains unclear. 21,28 In this study, we found that inhibition of PLC activation and chelation of intracellular Ca 2ϩ ions by treatment with U73122 and BAPTA-AM resulted in a significant reduction in S1P-induced migration and tube formation, as well as Ca 2ϩ influx to lymphatic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…HKa and recombinant D5 (also named kininostatin, Ref. 103) inhibit proliferation, migration, and survival of cultured endothelial cells (103, 226,277,640). Inhibition of endothelial cell proliferation is Zn 2ϩ dependent and interferes with the mitogenic effects of bFGF, VEGF, HGF, and PDGF (640) by blocking the transition from G 1 to S phase of the cell cycle (226).…”
Section: Cleaved High-molecular-weight Kininogenmentioning
confidence: 99%